Analysis of multiple failure behaviors of steering knuckle ball hinge of multi-axle heavy vehicle. Issue 1 (August 2021) - Wang, Zhenyu; Wei, Shuo; Bao, Ke; Peng, Senye; Zhang, Qing
Abstract: The ball hinge is a key component of the vehicle chassis that connects the steering knuckle and the control arm. This study analyzed the multiple failure behaviors of the chassis ball hinge. First, according to the macroscopic failure characteristics of the ball hinge, the analysis method of the fault tree was adopted to identify the possible cause of the failure. The axial force and radial force of the ball joint were obtained by simulating the force of the vehicle under the typical extreme conditions. The stress distribution of the ball pin was obtained by finite element analysis of the ball joint. The calculation results are consistent with the fatigue crack position of the ball hinge. Then the ball hinge was disassembled. On the one hand, the macro morphology was observed. On the other hand, the chemical composition and microstructure of the ball pin material were analyzed by scanning electron microscope and infrared spectrum analyzer. Finally, the macro morphology and microstructure of the ball joint seat, ball bowl, dust cover and other parts matched with the ball hinge were analyzed to further verify the failure reason of the ball hinge. The results showed that the dust cover of the ball hinge was firstly aged and cracked, and the external dust and particles enter into the friction contact area of the ball hinge, which caused the ball pin and ball bowl to be stuck. During the driving process of the vehicle, the ball pin undergoes unidirectional bending fatigue fracture in the stress concentration area at the root of the conical surface.